Taxonomy and natural history of the poorly known Dindigul shieldtail Uropeltis dindigalensis (Beddome, 1877) (Serpentes: Uropeltidae) - Ganesh, S.r.; Sampaio, Filipa L.; Gower, David J. (Zootaxa, 2022)
Uropeltis dindigalensis (Beddome, 1877) is a poorly known uropeltid (shieldtail) snake from peninsular India. Here we report morphological data for 14 preserved and nine uncollected specimens, most of which have not been previously reported. We designate a lectotype from the type series, describe it, and present the first published photographs of some of the type material. Recharacterization of U. dindigalensis clarifies its taxonomic distinctiveness and its geographical distribution. We report new natural-history observations from museum specimens and of individuals in life, including viviparity and feeding behaviour. The species is known only from the higher elevations of Sirumalai hills, in the southern end of the Eastern Ghats. Uropeltis dindigalensis appears somewhat capable of tolerating low-intensity agriculture. The main immediate conservation threats are probably greater intensity human activities, including road traffic, and possibly climate change given that the species is restricted to the uppermost elevations of a small hill range. The very small extent of occurrence within a single threat-defined location (none of which lies within a protected area), combined with decreasing quality and quantity of habitat, likely qualifies U. dindigalensis as Critically Endangered (or, at best, Endangered) under IUCN Red List criteria.